Evaluasi Usability Aplikasi Mobile KAI Access Menggunakan Metode System Usability Scale (SUS) Dan Discovery Prototyping (Studi Kasus PT KAI) - Adena Nioga; Komang Candra Brata; Lutfi Fanani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
PT Kereta Api Indonesia is a business entity owned by Indonesia transportation service provider namely train,along with the time PT KAI is quite aware of the importance of a mobile application to provide online services. with this application is expected to providing convenience in accessing and conducting transactions,but the reality application users provided by PT KAI is KAI Access application is quite low based on the rating and user response on the PlayStore. this shows that the value of Usability KAI Access is quite low it is necessary to conduct research by testing and improvement in usability aspects.In measuring the quality of an application can be done by measuring usability value.in this research was conducted using usablity technique,with usability questionnaire the name is Syestem Usablity Scale (SUS)method,it can measuring user satisfaction after doing testing by assigning tasks performed by respondents using the Access KAI application and make improvements with using Discovery Prototyping method as suggestion for improvements whic conducting by interview the users,the give recommendation with using prototype and do testing again then compare it.The result obtained from testing performed get result of usability value KAI Access aplication is 57.48% and after re-testing with using prototype from improvement recommendation suggest get result of 83,03%.